2018
DOI: 10.1186/s41935-018-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

The opinions of senior nursing students about forensic nursing

Abstract: Background: Today, the increasing number of crime and violence cases is defined as a universal health problem and nurses are the first healthcare personnel to encounter victims and offenders in hospitals, emergency units, intensive care, and services, even at policlinics or on-scene; therefore, it is important that nurses receive education in forensic nursing. Methods: This study was conducted as a descriptive study to determine the opinions of senior nursing students about forensic nursing. This study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
6
0
4
Order By: Relevance
“…Another study conducted by Gökdoğan and Erkol (2005) with nurses and nursing instructors revealed that 83.8 percent of the participants had no idea about forensic nursing and the duties of forensic nurses [9]. In a study, Topçu and Kazan (2018) have asked students about their opinions on forensic nursing, 94.7% of the students stated that there should be a field of forensic nursing in Turkey, and 42.1% of them stated that elective courses on forensic nursing should be offered in college [19]. The results of the study clearly show that nurses do not have sufficient knowledge about forensic nursing in our country.…”
Section: Discussionmentioning
confidence: 98%
“…Another study conducted by Gökdoğan and Erkol (2005) with nurses and nursing instructors revealed that 83.8 percent of the participants had no idea about forensic nursing and the duties of forensic nurses [9]. In a study, Topçu and Kazan (2018) have asked students about their opinions on forensic nursing, 94.7% of the students stated that there should be a field of forensic nursing in Turkey, and 42.1% of them stated that elective courses on forensic nursing should be offered in college [19]. The results of the study clearly show that nurses do not have sufficient knowledge about forensic nursing in our country.…”
Section: Discussionmentioning
confidence: 98%
“…Alguns artigos evidenciam a lacunas de conhecimento de estudantes de enfermagem quanto a conceitos de enfermagem forense, campo de atuação profissional, assuntos relacionados à medicina legal [18][19] .…”
Section: Discussão O Ensino De Enfermagem Forense No Campo Assistencial E Da Pesquisaunclassified
“…Em visto disso, é necessário que as universidades invistam em programas de ensino, pesquisa e extensão que acrescentem ou valorizem os conteúdos curriculares, diante da necessidade de os enfermeiros buscarem programas de especialização na área de medicina legal bem como façam pesquisas para melhor reconhecimento dessa área nos campo de assistência e do ensino de enfermagem 17,18,19 .…”
Section: Discussão O Ensino De Enfermagem Forense No Campo Assistencial E Da Pesquisaunclassified
“…Araştırmada, öğrencilerin çoğunluğu adli hemşirelik denilince akıllarına gelen ilk kelimenin "adli vaka/olay" ikinci sırada ise "otopsi" olduğunu ifade etmişlerdir. Konuya ilişkin yapılan çalışmalarda benzer şekilde, hemşirelik öğrencilerinin adli hemşireliği en çok "otopsi" kavramı ile eşleştirmiş oldukları ortaya çıkmıştır (12,18). Otopsi adli hemşirenin görevleri arasında yer almamaktadır (19).…”
Section: Tartişma Ve Sonuçunclassified